Sex and vanity eaudiobook A gma book club pick: a novel. - Kwan, Kevin (Random House Audio, 2020)
NEW YORK TIMES BEST SELLER • A Good Morning America Book Club Pick "Kevin Kwan's new book is his most decadent yet." — Entertainment Weekly The iconic author of the bestselling phenomenon Crazy Rich Asians returns with the glittering tale of a young woman who finds herself torn between two men: the WASPY fiancé of her family's dreams and George Zao, the man she is desperately trying to avoid falling in love with. On her very first morning on the jewel-like island of Capri, Lucie Churchill sets eyes on George Zao and she instantly can't stand him. She can't stand it when he gallantly offers to trade hotel rooms with her so that she can have a view of the Tyrrhenian Sea, she can't stand that he knows more about Casa Malaparte than she does, and she really can't stand it when he kisses her in the darkness of the ancient ruins of a Roman villa and they are caught by her snobbish, disapproving cousin Charlotte. "Your mother is Chinese so it's no surprise you'd be attracted to someone like him," Charlotte teases. The daughter of an American-born Chinese mother and a blue-blooded New York father, Lucie has always sublimated the Asian side of herself in favor of the white side, and she adamantly denies having feelings for George. But several years later, when George unexpectedly appears in East Hampton, where Lucie is weekending with her new fiancé, Lucie finds herself drawn to George again. Soon, Lucie is spinning a web of deceit that involves her family, her fiancé, the co-op board of her Fifth Avenue apartment building, and ultimately herself as she tries mightily to deny George entry into her world—and her heart. Moving between summer playgrounds of privilege, peppered with decadent food and extravagant fashion, Sex and Vanity is a truly modern love story, a daring homage to A Room with a View, and a brilliantly funny comedy of manners set between two cultures.